2018
DOI: 10.1371/journal.pone.0195553
|View full text |Cite
|
Sign up to set email alerts
|

Gα-cAMP/PKA pathway positively regulates pigmentation, chaetoglobosin A biosynthesis and sexual development in Chaetomium globosum

Abstract: Sensing the environmental signals, the canonical Gα-cAMP/PKA pathway modulates mycelial growth and development, and negatively regulates some secondary metabolism in filamentous fungi, e.g. aflatoxin in Aspergillus nidulans. Here we report the characterization of this signaling pathway in Chaetomium globosum, a widely spread fungus known for synthesizing abundant secondary metabolites, e.g. chaetoglobosin A (ChA). RNAi-mediated knockdown of a putative Gα-encoding gene gna-1, led to plural changes in phenotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…DEGs between the wild-type strain and pG14 were selected based on FDR < 0.001 and |log 2 Ratio| ≥ 1. In pG14, among a total of 3326 DEGs, 688 were upregulated and 2638 were downregulated [ 34 ]. The result of the transcriptome analysis done by RNA-seq as a complementary data in our previous work is online (10.1371/journal.pone.0195553.s004).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…DEGs between the wild-type strain and pG14 were selected based on FDR < 0.001 and |log 2 Ratio| ≥ 1. In pG14, among a total of 3326 DEGs, 688 were upregulated and 2638 were downregulated [ 34 ]. The result of the transcriptome analysis done by RNA-seq as a complementary data in our previous work is online (10.1371/journal.pone.0195553.s004).…”
Section: Resultsmentioning
confidence: 99%
“…One of the targets of the heterotrimeric G protein is the enzyme adenylyl cyclase that converts ATP to cAMP for use as a secondary messenger in filamentous fungi, as in other eukaryotic organisms [ 24 27 ]. Previous work revealed that intracellular levels of cAMP were modulated in a Gna1-dependent manner in C. globosum [ 34 ]. The cAMP level in the pG14 mutant was clearly reduced relative to that in the wild-type strain, while pGP6 increased cAMP accumulation nearly to the wild-type level [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations